Unraveling climatic changes from intraprofile variation in oxygen and hydrogen isotopic composition of goethite and kaolinite in laterites: an integrated study from Yaou, French Guiana - Girard, Jean-Pierre; Freyssinet, Philippe; Chazot, Gilles (Geochimica et cosmochimica acta, 2000)
An integrated study of O and H isotopes in the lateritic profile of Yaou, French Guiana, was undertaken to investigate the usefulness of stable isotopes as tracers of climatic changes in continental environments. The studied profile is composed of a 27 m thick saprolite, mostly developed in the past under wet-and-dry tropical climate in association with a duricrust, overlain by a 3 m thick yellow latosol formed more recently under present equatorial hot and humid climate. δ 18O–δD values determined for weathering goethite (pseudomorphs after pyrite) and kaolinite (microcrystalline clay groundmass) throughout the 30 m deep profile reflect formation temperatures consistent with present (25°C) and realistic past climatic temperatures (20°C–30°C), indicating that weathering minerals formed in isotopic equilibrium with their genetic environment and were not subjected to significant isotope exchange after formation. A distinct shift downward (2‰ for δ 18O, 15‰ for δD) from low to high δ 18O–δD values occurs around 20 m depth in the saprolite. It is interpreted as recording the change from the past tropical to the present equatorial climate. Goethite and kaolinite in the 5–10 m thick saprolite interval immediately above the active basement weathering front are in isotopic equilibrium with modern water and must have formed under present equatorial-humid conditions. In contrast, goethite and kaolinite found higher up in the saprolite and in the duricrust formed in the past under tropical wet and dry climate from waters distinctly depleted in 18O and D relative to modern water. The marked depletion of paleo-meteoric water at Yaou most likely reflects a more contrasted or “monsoonal” character of the ancient tropical climate. The present study shows that ancient weathering minerals in lateritic profiles preserve their δ 18O–δD values and carry a time signal. The time signal is best expressed in minerals formed rapidly at the weathering front and not subjected to post-formational remobilization, such as the goethite pseudomorphs after pyrite occurring at Yaou. Groundmass kaolinite is more susceptible to partial remobilization, through successive dissolution-precipitation reactions, which may obliterate the paleoclimatic signal. Unraveling the climatic record carried by weathering minerals in old soil systems is greatly enhanced by studying both oxygen and hydrogen isotopic compositions.